1995
DOI: 10.1128/jb.177.1.134-143.1995
|View full text |Cite
|
Sign up to set email alerts
|

In vivo restriction by LlaI is encoded by three genes, arranged in an operon with llaIM, on the conjugative Lactococcus plasmid pTR2030

Abstract: The LlaI restriction and modification (R/M) system is encoded on pTR2030, a 46.2-kb conjugative plasmid from Lactococcus lactis. The llaI methylase gene, sequenced previously, encodes a functional type IIS methylase and is located ϳ5 kb upstream from the abiA gene, encoding abortive phage resistance. In this study, the sequence of the region between llaIM and abiA was determined and revealed four consecutive open reading frames (ORFs). Northern (RNA) analysis showed that the four ORFs were part of a 7-kb opero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 43 publications
2
50
0
Order By: Relevance
“…These have been subdivided as type IIs systems. A lactococcal example of a type IIs R\M system is the LlaI system from the conjugative plasmid pTR2030 (O'Sullivan et al, 1995). This system also differs from other type II R\M systems because the restriction activity is encoded by three genes rather than one.…”
Section: Abbreviations : Abi Abortive Infection ; R/m Restriction/mmentioning
confidence: 99%
“…These have been subdivided as type IIs systems. A lactococcal example of a type IIs R\M system is the LlaI system from the conjugative plasmid pTR2030 (O'Sullivan et al, 1995). This system also differs from other type II R\M systems because the restriction activity is encoded by three genes rather than one.…”
Section: Abbreviations : Abi Abortive Infection ; R/m Restriction/mmentioning
confidence: 99%
“…In a previous study, a 13.6-kb BglII fragment of pTR2030 was cloned into shuttle vector pSA3 to produce plasmid pTK6 (30). This fragment encodes the phage resistance determinants for the LlaI restriction/modification operon and also carries the abortive gene abiA (26,39). However, phage resistance from pTK6 (EOP of 10 Ϫ4 with phage 31) is expressed at a lower level than that from pTR2030 (EOP of Ͻ10 Ϫ10 with phage 31) (32).…”
Section: Resultsmentioning
confidence: 99%
“…Plasmid pTR2030 has previously been partially subcloned and sequenced to reveal an R/M system, LlaI, and the abortive gene abiA (originally designated hsp) (26,39). However, testing of AbiA and R/M subclones of pTR2030 suggested that a third mechanism could be encoded on this plasmid (27,32,39,42). Additional subcloning and sequencing of pTR2030 revealed a novel abortive resistance mechanism downstream of abiA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…R/M systems are the most frequently encountered resistance mechanism in Lactococcus, where they are typically plasmid-encoded (Hill, 1993 ;Klaenhammer & Fitzgerald, 1994;Garvey et al, 1995). The nucleotide sequences of three complete systems have been pub-0002-1 480 0 1997 SGM lished: LlaI (Hill et al, 1991;O'Sullivan et al, 1995), LlaDCHI (previously referred to as LlaII; Moineau et al, 1995) and LlaBI (Nyengaard et al, 1996). In addition, the sequences of two chromosomally encoded methyltransferases (MTases) associated with the ScrFI R / M system from L. lactis subsp.…”
Section: Introductionmentioning
confidence: 99%